Bibliometric and visual analysis of chronic stress in cancer research from 2014 to 2024 - Zhuheng Wei; Anxia Li; Ling Su; Bo Zhang; Yuanyuan Yan (Discover Oncology)
Abstract Objective In today's fast-paced society, stress has become a widespread phenomenon, garnering increasing attention for its impact on cancer. This study aims to investigate the current status and research hotspots of chronic stress in cancer research from 2014 to 2024, with the goal of providing valuable insights for future studies. Methods We retrieved 618 articles published between 2014 and 2024 from the Web of Science database and analyzed them using R software, VOSviewer, and CiteSpace. Results There is an overall upward trend in chronic stress-related cancer research, with China leading in publications, followed by the United States, India, Australia, and Italy. The journal most cited is Brain Behavior and Immunity. Key themes identified include 'inflammation', 'breast cancer', 'anxiety', 'psychological stress', and 'oxidative stress'. The primary focus of the research is the impact of chronic stress on various cancer types, the underlying molecular mechanisms, and the implications of chronic stress-related treatments on cancer outcomes. Conclusion Chronic stress is increasingly recognized as a Carcinogenic factors. This study provides a comprehensive analysis of chronic stress-related cancer research from 2014 to 2024, offering valuable guidance for future research in this field.